A review on flocculation as an efficient method to harvest energy microalgae: Mechanisms, performances, influencing factors and perspectives. (October 2020) - Li, Shuangxi; Hu, Tianyi; Xu, Yanzhe; Wang, Jingyi; Chu, Ruoyu; Yin, Zhihong; Mo, Fan; Zhu, Liandong
Abstract: The energy demands and costs of harvesting microalgal biomass make it unrealistic and unsustainable for economically feasible microalgal biofuel production. Therefore, meticulous exploration of the harvesting processes is essential to identify appropriate harvesting techniques for potentially commercialized microalgal biodiesel production. Flocculation may be a superior method when considering harvesting efficiency, economic cost, energy consumption and technical feasibility. This review sheds some light on the recent progresses of physical/chemical flocculation and bioflocculation applied in the microalgal biomass harvesting processes. Physical flocculation techniques are energy-intensive and require special equipment, creating the cost barrier for microalgal biomass harvesting. Magnetic particle flocculation is much more efficient and is also recyclable. In contrast, chemical flocculation that involves the application of organic and inorganic flocculants, is now in the limelight. The microalgae species applied, the dosages of flocculants as well as flocculation recovery efficiencies are compared and presented in detail in this review. In addition, bioflocculation as a harvesting techniques is critically described, in particular the mechanisms of autoflocculation, a promising bioflocculation by co-cultivation of microalgae with microorganisms, are explored. This review also disclosed the effects of flocculant application on downstream processes, especially when chemical flocculants are applied. This review intends to provide guidance for the long-term adoption of these economically beneficial mature flocculation recovery technologies in the biofuel industry. Despite of considerable progress, key challenges such as further reduction of costs and the minimization of downstream product pollution risks in conventional and advanced harvesting techniques, must be addressed. This article also suggests the directions for future research in microalgae harvesting and argues that the production of microalgae biofuels under potential policy intervention should be carried out in a healthy and sustainable way. Graphical abstract: Image 1 Highlights: As a potential substitute for fossil fuel, microalgae biofuel has great significant application prospects. The high cost of the harvesting process is the main bottleneck in microalgae biofuel production. The selection of microalgae harvesting technologies is advised to ensure the sustainable development of biofuels. The systematic policy guarantees the successful large-scale application of the microalgae biofuel industry.